Eu (e nós) proteano: funções retóricas da primeira pessoa do discurso e a construção de ethos em dossiês das revistas Cult e Nova Águia - Bini, Renan Paulo (2023)
This research is justified by developing analysis of rhetorical functions of First Person Singular (FPS) and First Person Plural (FPP) in texts in the Portuguese language written modality and by proposing the classification of marks and mobilizers of FPS and FPP, used for the construction of ethos, in a gradual rhetorical scale, in texts of the dossier genre The objective is to verify how the FPS and the FPP are used for the construction of ethos in dossiers published in 2018: three about personalities of Portuguese culture and literature, from the magazine Nova Águia, from Portugal; and three about personalities of Brazilian culture and literature, from the magazine Cult, from Brazil. The corpus is composed of clippings with occurrences of FPS and FPP based on the following research questions: 1) In what way do FPS and FPP perform rhetorical functions for the realization of ethos in the corpus? 2) Is there a prevalence of marks and mobilizers of ethos construction, if we compare the occurrences of FPS and FPP in the clippings of the dossiers from Cult and Nova Águia? This research is descriptive and exploratory in nature. For the analysis, it was adopted, mainly, the qualitative perspective, theoretically based on studies of different strands of Linguistics, Pragmatics and Rhetoric. Basically, We follow the authors Benveniste (1991), Fiorin (1996, 2001), Tang and John (1999), Lucchesi (2009), Posio (2011), Manetti (2015), Screti (2015), Stewart (2015), Manetti (2015), Marques and Ramos (2015), Marques and Duarte (2016), Soares (2016), Fauci (2016), Maurizi (2017), Fowler and Kress (2019), and Taylor and Goodall (2019) were followed. This theoretical basis provided the verification of recurrence of mobilizers and linguistic marks of the studied phenomena, and, in a second moment, provided the descriptive statistical analysis. The results show that FPS and FPP indicate a posture of the text producer, since they represent the ethos that is being built through linguistic resources that serve the argumentative purposes of the text producer and stage images of the same producer. In the texts analyzed, there are six marks linked to FPP for the construction of ethos and one linked to FPS. We also identified ten strategies to activate the First Person of the Speech (incident mobilizers), which mobilize the construction of ethos in the dossiers, and gradually anchor what is said to the image projected by the producer. Some different constructions of ethos in the clippings of the dossiers of Cult and Nova Águia magazines were contingent, possibly by cultural and socio-historical factors of constitution of the different audiences (Brazilian readers and Portuguese readers) and by the historical and/or affective proximity between the producers and the honored personalities.